85.4k views
2 votes
-3/4x+5/6y=15
x-intercept=
y-intercept=

User Enricog
by
4.9k points

1 Answer

3 votes

To make this easier, you need to change the fractions by multiplication.

-3/4x=15 - First, you multiply 4 to both sides of the equation

(4)-3/4x=15(4)

-12/4x=60 - Simplify

-3x=60 - Divide by -3 on both sides

x=-20 -> (-20,0)

Do the same to find the y-intercept, to get (0,18)

User Walter Rumsby
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.